Role of mutations and post-translational modifications in systemic AL amyloidosis studied by cryo-EM - Radamaker, Lynn; Karimi-Farsijani, Sara; Andreotti, Giada; Baur, Julian; Neumann, Matthias; Schreiner, Sarah; Berghaus, Natalie; Motika, Raoul; Haupt, Christian; Walther, Paul; Schmidt, Volker; Huhn, Stefanie; et al. (Nature Communications, 2021)
Systemic AL amyloidosis is a rare disease that is caused by the misfolding of immunoglobulin light chains (LCs). Potential drivers of amyloid formation in this disease are post-translational modifications (PTMs) and the mutational changes that are inserted into the LCs by somatic hypermutation. Here we present the cryo electron microscopy (cryo-EM) structure of an ex vivo λ1-AL amyloid fibril whose deposits disrupt the ordered cardiomyocyte structure in the heart. The fibril protein contains six mutational changes compared to the germ line and three PTMs (disulfide bond, N-glycosylation and pyroglutamylation). Our data imply that the disulfide bond, glycosylation and mutational changes contribute to determining the fibril protein fold and help to generate a fibril morphology that is able to withstand proteolytic degradation inside the body.